Kids and the VIC. - Carlson, Edward H.; Trap, Paul D. ([Chatsworth, CA] Datamost, 1982)
Lessons for programming in BASIC on a VIC 20 computer using games and assignments.
Includes indexes.
Keywords: VIC 20 (Computer) -- Programming -- Juvenile literature; BASIC (Computer program language) -- Juvenile literature; VIC 20 (Computer) -- Programming; BASIC (Computer program language); Programming (Computers)